The role of S100A9 as a diagnostic and prognostic biomarker in septic shock - Yingxue Hu; Qinghui Yang; Xiao Liu; Li Yuan; Fang Yan; Yang Li; Pingwei Ni (PLoS ONE, 2025)
Background Sepsis is a severe and potentially fatal systemic condition marked by excessive immune defense against infection. Within this research, we explored the serum concentration of S100A9 during hospital admission, aiming to assess its role and reliability as a viable biomarker for identifying septic shock and predicting mortality risk in sepsis. Furthermore, we explored whether combining S100A9 with conventional assessment tools could enhance diagnostic precision and prognostic accuracy, offering valuable insights to support early intervention and personalized treatment strategies for sepsis. Methods This study comprised 575 participants overall, with sepsis patients classified into non-shock and shock groups based on the severity of their condition. Additionally, age- and gender-matched ICU control cohort and healthy control group were recruited to ensure wide applicability and strong comparability of the findings. Enzyme-linked immunosorbent assay utilized for detecting serum S100A9 levels in subjects within 24 hours of admission, ROC curves were used to evaluate the disease identification and prognostic analysis. Differences in survival outcomes among patients with varying levels of S100A9 expression were analyzed using the Kaplan-Meier method. Results Serum S100A9 concentrations were elevated in septic patients upon admission. In the diagnosis of patients with septic shock, S100A9 performed similarly to APACHE II, and a considerable enhancement was noted in the sensitivity of detecting septic shock when S100A9 was combined with lactate and APACHE II. At the initiation of ICU stay, the area under the receiver operating characteristic curve (AUC) for the association between serum S100A9 levels and 28-day mortality was 0.78. This value surpassed the AUCs for IL-6 (0.66), procalcitonin (0.60), lactate (0.58) and C-reactive protein (0.47). Furthermore, septic patients with elevated serum S100A9 levels (≥ 630.77 pg/ml) exhibited lower survival rates compared to those with lower concentrations (< 630.77 pg/ml). Conclusion S100A9 is a promising biomarker for diagnosing septic shock and forecasting clinical outcomes in patients with sepsis. In addition, S100A9 has good predictive efficacy for the risk of death in sepsis patients.